2021
DOI: 10.1111/itor.13012
|View full text |Cite
|
Sign up to set email alerts
|

Policy evaluation and efficiency: a systematic literature review

Abstract: This paper provides a systematic literature review of studies investigating the effect of an intervention on the efficiency of a decision-making unit, when efficiency is computed using nonparametric frontier approaches. This paper offers a guide for future research by identifying patterns in (1) the fields of application, (2) applied efficiency models, and (3) analysis of efficiency determinants. Our findings indicate that, despite the prominent role of frontier techniques in the analysis of public sector perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 144 publications
0
32
0
2
Order By: Relevance
“…Studying how to perform unbiased measures of efficiency and explaining the mechanisms through which public interventions and shocks of various types affect the economy is fundamental for both policymakers and several other stakeholders (Mergoni and De Witte, 2022). Furthermore, market players, institutions, and citizens involved in some key sectors are particularly concerned with understanding the impacts of both institutional and noninstitutional changes on their performance.…”
Section: Methodsmentioning
confidence: 99%
“…Studying how to perform unbiased measures of efficiency and explaining the mechanisms through which public interventions and shocks of various types affect the economy is fundamental for both policymakers and several other stakeholders (Mergoni and De Witte, 2022). Furthermore, market players, institutions, and citizens involved in some key sectors are particularly concerned with understanding the impacts of both institutional and noninstitutional changes on their performance.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring efficiency of public entities is an ancient challenge, therefore, different methods have been developed trying to consolidate concepts and practices. The available bibliography is quite comprehensive in terms of theoretical discussion, however, unified practical methodologies designed to provide step-by-step evaluation technics remain as a structural need for public accounting improvement (Jääskeläinen & Laihonen, 2014;Maurel et al, 2014;Mergoni & De Witte, 2021;Van Dooren et al, 2012). Mihaiu et al (2010) simply defines efficiency as the ratio between outcome effects and efforts made.…”
Section: Bibliographic Backgroundmentioning
confidence: 99%
“…Therefore, efficiency reports play a crucial role in improving social welfare. However, measuring and reporting efficiency remains a challenge extensively discussed by the international academy (Afonso et al, 2013;Curristine et al, 2007;Mergoni & De Witte, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sommersguter-Reichmann (2020) concentrated on the incorporation of quality in nonparametric frontier efficiency studies, which have attracted considerable attention since the seminal works of Farrell (1957), Charnes et al (1978), as well as Färe and Knox Lovell (1978). The extensive bibliographies (e.g., Seiford 1996; Emrouznejad and Yang 2018), general and health-related reviews (e.g., Peykani et al, 2021, Mergoni and Witte 2021, Hollingsworth 2008, Cantor and Poh 2017, O'Neill et al 2008, Kohl et al 2019) and special issues (e.g., Emrouznejad et al 2019;Emrouznejad 2014;Jablonsky et al 2018) underpin the dynamic publication activity in this field. The author found that many studies assume that structural quality affects inefficiency distribution.…”
Section: Health Economic Applicationsmentioning
confidence: 99%